2021
DOI: 10.1097/ta.0000000000003264
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of single dose liposomal bupivacaine versus indwelling analgesic catheter in patients undergoing surgical stabilization of rib fractures

Abstract: Locoregional analgesia (LRA) remains underused in patients with chest wall injuries. Surgical stabilization of rib fractures (SSRF) offers an opportunity to deliver surgeon-directed LRA under direct visualization at the site of surgical intervention. We hypothesized that a single-dose liposomal bupivacaine (LB) intercostal nerve block provides comparable analgesia to an indwelling, peripheral nerve plane analgesic catheter with continuous bupivacaine infusion (IC), each placed during SSRF. METHODS:Noninferiori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…By contrast, in our study, both patient and physician were blinded to treatment regimen further minimizing bias in the results. Further, a recent study by Leasia et al 32 provided more evidence that single injection of liposomal bupivacaine provides comparable analgesia to a continuous peripheral nerve plane analgesia catheter in patients undergoing rib fracture surgical stabilization with no significant reductions in opiate use.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in our study, both patient and physician were blinded to treatment regimen further minimizing bias in the results. Further, a recent study by Leasia et al 32 provided more evidence that single injection of liposomal bupivacaine provides comparable analgesia to a continuous peripheral nerve plane analgesia catheter in patients undergoing rib fracture surgical stabilization with no significant reductions in opiate use.…”
Section: Discussionmentioning
confidence: 99%
“…Sheets et al found that traumatic rib fracture patients receiving ICNB with liposomal bupivacaine were intubated less frequently and had shorter intensive care unit and overall hospital stays than patients with TEA ( 10 ). Similarly, a randomized controlled trial demonstrated that a single liposomal bupivacaine block provided comparable pain control to an indwelling peripheral analgesic catheter placed in a similar space for patients undergoing surgical stabilization of rib fractures ( 11 ). Another large retrospective analysis of patients undergoing abdominal surgery discovered that patients who received liposomal bupivacaine blocks had shorter lengths of stay, lower rates of readmission and lower rates of post-surgical hypotension and vasopressor use than those who received epidural analgesia ( 12 ).…”
mentioning
confidence: 99%